Working Conditions in Pharmacies in the Republic of Serbia - Ćirović, Tijana (Archives of Pharmacy, 2022)
The goal of this paper was to address issues in the pharmaceutical practice, from the community pharmacists’ point of view with the emphasis on working conditions. The survey was conducted in May 2022 and included 180 pharmacists from all around Serbia, using an online questionnaire. The sample included pharmacists from different types of pharmacy chains (42% participants worked in big chains with more than 100 pharmacies and 19.9 % worked in small chains, with less than 10 pharmacies). The majority declared that they had a salary between     81000 RSD and 110000 RSD, with half of them more than 91000 RSD. 78.5% participants said that they worked alone in a shift, and 70.5% said that they could not have a 30-minute break without interruption. They were asked if they worked more than 48 hours per week, and 40.7% participants answered “Yes”. 78% of them said that they often worked at weekends and/or during holidays. Only 12.4% of pharmacists dedicate more attention to patients than administrative and other tasks. One third of the participants (29%) were completely or particularly dissatisfied with working conditions and 74% said that they would leave their job as soon as they got a better opportunity. The survey results show that there is a need to improve working conditions in pharmacies. We need to work on the education and improving of competences of pharmacists along with improving working conditions: reducing workload during weekends and holidays, hiring staff, and ensuring better salaries to get more motivated and satisfied pharmacists.